Analisa Perbandingan SAW, WP, dan TOPSIS Dalam Penentuan Hotel Terbaik - Fahrizal Artha Pangestu; Nugroho Dwi Susanto; Angga Sanjaya Syahputra; Daffa Putera Zawahir; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
A hotel is one that operates as a guest facility. In this study, the authors aim to design and build a decision support system for selecting the best hotel. The author uses 4 criteria. Namely, hotel room rental rates, hotel location, hotel cleanliness and hotel services. The result obtained is a hotel selection decision support system that is able to help visitors to choose a hotel among the many existing hotels. In determining the best hotel, a decision support system will be made using the Simple Additive Weighting (SAW) method, the Weighted Product (WP) method and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). With the existence of a decision support system, it is hoped that it can assist visitors in choosing hotels that match the desired criteria.